P1_1 Hollywood Sign Illuminations: Is it Worth the Money? - Reed, Lisa; Fitzpatrick, Amber; Vanderpump, Phoebe; Mahon, Hannah (Physics Special Topics, 2022)
In this paper, an investigation is conducted as to whether it is financially viable for the famous Hollywood sign in California to be lit up by Light Emitting Diodes (LEDs) for 12 hours. By estimating the surface area of the Hollywood sign, we calculated the number of LEDs required to fully cover the sign and the power of each LED. We estimated the cost to illuminate the Hollywood sign for 12 hours to be approximately $11,000 (2s.f.). Therefore, we think it is financially viable to illuminate the Hollywood sign for a single event. However, considering installation and maintenance costs we do not think this would be a financially viable project for long term use.